2011
DOI: 10.1007/s11195-011-9204-x
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Knowledge and Behavior of Adolescent Male and Female Students in Turkey on the Matter of Reproductive Health

Abstract: In this research, the objective is to determine the level of knowledge, the sources of information and the behavior of adolescent male and female students in Turkey on the matter of reproductive health. The sample is comprised of 600 students randomly chosen from four different elementary schools. The survey form was used for data collection. In analyzing the data, we calculated averages and performed Chi-square tests. We determined that 82.3% of the students are aware of the changes in their own bodies, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Our study took place in central Istanbul and the average age of menarche was found to be 12.9 years. Although there is a debate about secular trends in puberty worldwide, our national reference data have shown that the age of menarche has not changed over the last 40 years ( 7 , 8 , 9 , 10 , 11 ). Also, age of menarche did not differ greatly from that in European countries or the USA ( 12 ).…”
Section: Discussionmentioning
confidence: 81%
“…Our study took place in central Istanbul and the average age of menarche was found to be 12.9 years. Although there is a debate about secular trends in puberty worldwide, our national reference data have shown that the age of menarche has not changed over the last 40 years ( 7 , 8 , 9 , 10 , 11 ). Also, age of menarche did not differ greatly from that in European countries or the USA ( 12 ).…”
Section: Discussionmentioning
confidence: 81%
“…4 The foremost vital changes that ensue in adolescents may be physical changes that ensue at a time of puberty. 5 Puberty may be a time of fast biological process where sexual and physical maturation occurs. 6,7 Puberty includes biological process, secretion and growth method that happens once organ begins to perform and therefore the secondary sexual characters start to develop.…”
Section: Introductionmentioning
confidence: 99%
“…8 The onset of menstruation and appearance of secondary sexual characters are the important changes that occur in adolescent girls. 5 In today's world, the lifestyle changes, particularly consumption of more junk foods, lack of physical activity and the amount of stress experienced by the students in the school life were considered to be some of the major factors for menstrual disturbances among the adolescent girls. The health status of adolescents reflect the health and well-being of the next generation.…”
Section: Introductionmentioning
confidence: 99%
“…Premarital sexual intercourse is forbidden to women, sometimes women are forced to take virginity examinations, even forced to marry the person they had sexual relation with and sometimes traditions impose extreme sanctions including putting to death. Despite these prohibitions against women, men are expected to have sexual activity at an early age [6,13,19,20,23,24]. The association of women's premarital sexual life with morality is a reflection of a despotic approach and this controls sexual lives of women.…”
Section: Introductionmentioning
confidence: 99%